Factors to adjust litter weight of pigs to a standard 21 days of age - Wood, C M; Christian, L L; Rothschild, M F (Journal of animal science, 1990)
Factors to standardize litter weights of nursing pigs to 21 d of age were calculated from daily weights measured on 64 crossbred litters from 10 to 32 d of age. The results were compared to published factors derived from a data set of Duroc pigs weighed every 3 to 4 d. Dams in the present study were white crossbred sows and gilts, and sires were maternal or terminal breed types. Multiplicative factors were calculated by dividing the mean 21-d litter weight (LW21) by mean daily litter weight. Linear and quadratic regression coefficients of LW21 on age at weighing were fitted to the factors (R2 = .997). The final equation for adjusting litter weights to a 21-d basis was 2.5246 - .1041 x (d of age) + .0015 x (d of age)2. There were good agreement with published factors for d 19 to 25, but divergence for younger and older litters resulted in significant differences between the linear coefficients. These differences may be due to departure from a linear growth curve, which daily measurements would incorporate, or differences in sow populations. Thus, use of the new factors should be considered for white crossbred sow populations. A least squares analysis indicated that LW21 was significantly altered by parity, not by the number of pigs allowed to nurse or by breed of sire. After adjustment to 21 d, litter weights also should be adjusted for differences in parity before evaluating sow productivity, by using additive factors such as those recommended by the National Swine Improvement Federation.